2023
DOI: 10.1063/5.0156669
|View full text |Cite
|
Sign up to set email alerts
|

On the polytropic coefficient of negative ions for modeling the sheath and presheath of electronegative plasmas

Abstract: The fluid description is widely used for the multi-dimensional modeling of low temperature plasmas with complex chemistries due to their relative low computational cost. It relies, however, on a series of simplifying assumptions and some truncation of the moment equations for describing the non-equilibrium between the electrons, positive ions, negative ions, and the neutrals. In this paper, the classical assumption of isothermal negative ions is revisited for electronegative plasmas and, more particularly, for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…The work of Das et al, 38 Laux et al, 39 and Zawaideh et al 40 deserve to be mentioned. Recently, Schiesko et al 41 analyzed the plasma-wall transition in a plasma containing positive ions, electrons, and negative ions. This work is characterized by the fact that the authors treated the positive and negative ions using the continuity, momentum transfer, and energy transfer equations, while the electrons were treated using the continuity and momentum transfer equations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The work of Das et al, 38 Laux et al, 39 and Zawaideh et al 40 deserve to be mentioned. Recently, Schiesko et al 41 analyzed the plasma-wall transition in a plasma containing positive ions, electrons, and negative ions. This work is characterized by the fact that the authors treated the positive and negative ions using the continuity, momentum transfer, and energy transfer equations, while the electrons were treated using the continuity and momentum transfer equations.…”
Section: Introductionmentioning
confidence: 99%
“…In this way, the polytropic function 42 was found for positive and negative ions. Schiesko et al 41 have shown that negative ions are not isothermal. However, they are still treated as isothermal in this paper, as only the continuity and momentum exchange equations are used to describe them.…”
Section: Introductionmentioning
confidence: 99%